(untitled) (Journal of Geography and Environmental Management, 2018)
This article deals with the theoretical problems of the development of Almaty city as agglomeration. Various criteria are applied for the allocation of urban agglomerations such as the density of the urban population and the continuity of development; the presence of a large city center (usually with a population of at least 100 thousand people); the proportion of non-agricultural workers; share of employees outside their place of residence; the number of urban satellite settlements and the intensity of their connections with the city center; production links; isochronal labor movements up to 1.5 or 2-hour from the city center, etc. The space-system problems of studying urbanized areas are considered on the example of the city of Almaty and its environs. The characteristics of urbanized areas as systems. Extensively researched and scientific analysis of the factors influencing on development of Almaty city as an agglomeration center. The zones of attraction (influence) of Almaty formed as the largest center of agglomeration in the country is determined, and its socio-economic characteristics are evaluated. Analyzing the works of foreign and domestic scientists, the main features of urban agglomeration are highlighted. The main directions of formation of urban agglomerations are determined. The data on the expansion of the city territory are analyzed and the structural and functional ties of the urban agglomeration are systematized. The main criteria listed in the strategic programs of the Republic of Kazakhstan are analyzed. Republic of Kazakhstan are analyzed. The main criteria for the development of Almaty city as agglomeration are determined.